The Greater Transformation: Digitalization and the Transformative Power of Distributive Forces in Digital Capitalism. Issue 4 (2nd October 2021) - Pfeiffer, Sabine
ABSTRACT: This article discusses digitalization and its connection with the political economy of transformation. Its point of departure is Karl Polanyi's historical analysis as presented in The Great Transformation . Polanyi analyzed the development of "self-regulating" markets—with transformative and destructive consequences for individuals, nature, and society—and government efforts to contain these consequences. Polanyi's perspective is compared to Marx's theorem of the development of productive forces. Their respective focal points are different but complementary. For Polanyi, the decisive historical and theoretical break (and the cause of the destructive effects) lies in the act of purchasing human labor, whereas for Marx it lies in the act of producing value and in the relations of production as well as the relations of distribution linked to it. Working from this theoretical basis, current developments in digitalization are analyzed not as a further development within productive forces but as a transforming development of distributive forces. Following the logic of The Great Transformation, current developments should thus not be interpreted as a second great transformation but as the augmentation of the first, leading to a "greater" transformation associated with even more destructive potential. This leaves little hope for a smooth transition into any form of post-growth society.